DESIGN AND SIMULATION THE VERY LOW HEAD TURBINE WITH HEAD 2 METER AND RATE OF FLOW 0,5 M3 /S USING FREE VORTEX CRITERIONS - SITORUS (NIM : 13107137); Pembimbing : Dr.Ir. Priyono Sutikno, SUPARMAN
Utilization of renewable energi sources such as mikrohydro in Indonesia is still small. The Very Low Head Turbine is one way of utilization of energi resources. This system has many advantages such as the use of renewable energi sources, low head, easy to maintenance, and have a simple civil construction. In my final project will be discussed about how to design of fixed blade and motion blade using free vortex criteria. The design of fixed blade and the blade motion is done using the program CASCADE. Modeling of turbine blades made by calculate t / l using the lift coefficient factor(model I) and using diffusion factor (model II). Theoretically obtained at 250 rpm produce power 8854.32 Watts, torque 338.21 Nm and efficiency 90%. The reason of using Computational Fluid Dynamics (CFD) in runner and guide vane design is to simulate and corrected the design. The simulation used the Fluent 6.3.26. The results of simulation model I at 250 rpm and mass flow 499.1 kg/s produce power of turbine 7025.612 Watt, head 1.86 m and efficiency77.103%.The parameter of simulation at constant mass flow of 499.1 kg/s highest efficiency 84.71% at 350 rpm.The parameter of simulation at constant rotation 250 rpm highest efficiency80.73% at 400 kg/s. The results of simulation model II at 250 rpmand mass499.1 kg/s produce power 4295.892 Watt, head 1.77 m, andefficiency 49.55%. The parameter of simulation at constant mass flow of 499.1 kg/s highest efficiency 52.23% at 300 rpm. The parameter of simulation at constant rotation 250 rpm highest efficiency 51.21% at 450 kg/s.